Evaluation of Land Capability and Land Use Direction In the Krueng Peusangan Hilir Sub-watershed, Bireuen Regency - Halim Akbar; Sarifuddin Sarifuddin; Sakral Hasby Puarada (Graduate Program of Syiah Kuala University, 2023)
The destruction of forests in watershed areas has now become a concern of many parties, resulting in floods, landslides, and droughts that continue to increase. Watershed damage is accelerated by increased utilization of natural resources due to population growth and economic development, conflicts of interest, and lack of integration between sectors between the upstream-middle-downstream areas. For this reason, it is necessary to assess land capability in a watershed so that land development follows the land capability class. The research was carried out in the Krueng Peusangan Hilir Sub-watershed, Bireuen Regency, Aceh, Indonesia, from October 2021 to February 2022, which is geographically located at 95°58''00” - 96°52''00” East Longitude and 5°06''00- 5°17 ''00